Approximate Solutions Of Transient Free - Convective Flow In A Vertical Channel Due To Symmetric Heating Using Laplace Transform Technique - I. ATHAL, M. K. SIVASANKARI (International Journal of Modern Agriculture, 2021)
This paper presents a closed form solution for transient free convective flow of a viscous and incompressible fluid in a vertical channel due to symmetric heating of channel walls. Laplace transform technique has been used to obtain the expression for velocity and temperature fields by solving the governing differential equations. The influence of physical parameters on the velocity field, skin-friction, rate of heat transfer and volumetric flux of fluid are carefully analysed. Correlation between steady state time and Prandtl number has been developed. It is observed that nature of correlation is linear when Prandtl number is greater than one while cubic for Prandtl number less than one. Also the analytical expressions here derived are in satisfactory.